The Illuminations of Faqe Qadir Hamawendy in Kurdish Literature - Ahmed, Dawlat M. (Humanities Journal of University of Zakho, 2018)
This research studies (the illuminations of faqe qadir Hamawendy in Kurdish literature) as he had great abilities with regard to nationalistic and revolutionary thoughts, on the other hand, the variety and diversity that existed in his life during that time is also worth considering throughout this paper. The importance of this paper lies in the fact that it is a practical, historical, and analytical paper. Likewise, this paper can benefit any researcher who has the desire to study the illuminations of Kurdish literature in general and to study the level of education of the poet faqe qadir Hamawendy in particular.